Characteristic Reconstitution of the Spinal Langerhans Cell Histiocytosis in Young Children. Issue 4 (April 2019) - Nakamura, Naoyuki; Inaba, Yutaka; Aota, Yoichi; Machida, Jiro; Saito, Tomoyuki
Abstract : Background: Pediatric Langerhans cell histiocytosis (LCH) often results in vertebral compression fracture. However, few reports have reported vertebral remodeling during the course of LCH. We aimed to investigate the longitudinal reconstitution and transformation of the affected vertebrae and the adjacent structures in young children with spinal LCH. Methods: We recruited 13 patients, including 16 affected vertebrae, diagnosed with LCH via biopsy. The average age at first visit was 3.6 years. The average follow-up period was 10.2 years. Vertebral lesions involved L2 in 3 cases; T12, L1, or L5 in 2 cases; and C4, C5, C7, T5, T8, T9, or L3 in 1 case. We measured the ratios of the height of the affected vertebra and 1 vertebra above the affected one to that of the second vertebra above the affected one, local kyphotic angles, and the ratio of the height of the center of the adjacent disk to that of one disk above it. Results: The collapse of the affected vertebra was most severe after 1 year of disease onset. The rate of reconstitution accelerated at 2 years or later of disease onset. The recovery speed of the anterior wall was faster than that of the center height. While the height of the affected vertebrae was restored, the thickness of the adjacent disk also increased. Further, the height of the adjacent vertebrae increased in a similar manner. The average local kyphosis angle shifted to lordosis within the first 3 years. Conclusions: The heights of not only the disk but also the adjacent vertebra increased during the vertebral collapse phase in pediatric spinal LCH patients. These transformations may affect the realignment of the sagittal spinal balance at the earlier stage of the disease. During the collapse phase, the heights of the adjacent vertebrae and disks increase but after the affected vertebrae reconstituted, the augmentation of adjacent vertebrae and disks diminished. Level of Evidence: Level IV. Abstract : Supplemental Digital Content is available in the text.